Dwelling with limits: the work of love in participatory research - Raine Aiava; Noora Pyyry (Fennia: International Journal of Geography)
In this article, we examine some of the theoretical and methodological challenges facing Participatory Action Research (PAR), including the continued challenge of the silence of the subaltern, the re-subjugating power relations in many traditional epistemologies of research production, and the problems of representation. We attempt to address these considerations by looking beyond the relational, outlining the originary call to ethics at the heart of PAR in terms of a commitment to a sustained engagement with that which outstrips relationality, namely the radical alterity of the other. Proposing a rigorous articulation of the concept of translation as a means of meaningfully and ethically thinking with the subaltern, disenfranchised, and at-risk — including young people — in PAR, we unpack Spivak’s articulation of a hesitant love in translation that is marked by a surrendering to the call of the other, and to the work of putting oneself into a position not to ‘speak for’ but to ‘hear from’ the unknowable, and un-preemptable other. Understanding love as a doing that affects, we outline the need to consider ‘action’ in PAR in terms of practice beyond happenings, representations, and method, to acknowledge the movements and shifts in the research encounter that refuse representational knowing. We add to this by outlining the researcher’s ontological indebtedness to this alterity by re-considering our notion of translation in terms of Heidegger’s trans-position, highlighting the ‘rhizovocality’ of the research encounter as fundamentally beyond any notion of authentic voice or settled subjectivities. In highlighting the ontological dependency inherent in the research encounter, we revisit the commitment of PAR as a work of being vulnerable — of putting ourselves into play by dwelling with the foreignness of the other, and in doing so, trans-posing ourselves unto new understanding.